Steel plates, components and their manufacturing methods
A steel plate with controlled composition and microstructure, combined with a specific manufacturing process, addresses the formability challenges of high-strength steel sheets, enhancing tensile strength, yield stress, and energy absorption for automotive impact members.
Patent Information
- Application Number
- JP2024534744
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-31
- Filing Date
- 2024-02-27
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-02-27
AI Technical Summary
Existing steel sheets with high tensile strength and yield stress face challenges in press formability, particularly in ductility, hole expandability, and bendability, leading to difficulties in forming impact energy absorbing members for automobiles without compromising energy absorption properties.
A steel plate composition with specific chemical elements and microstructural control, including controlled area ratios of ferrite, retained austenite, and tempered martensite, along with a surface soft layer, combined with a manufacturing process involving hot rolling, annealing, rapid heating, and galvanizing, to achieve high tensile strength, yield stress, and excellent formability and energy absorption.
The steel plate achieves tensile strength of 1180 MPa to 1470 MPa, high yield stress, and excellent press formability, bendability, and energy absorption, making it suitable for impact energy absorbing members in automobiles.
Smart Images

Figure 0007616490000008 
Figure 0007616490000001 
Figure 0007616490000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel plate, a member made of the steel plate, and a method for producing the same. [Background technology]
[0002] From the viewpoint of protecting the global environment, improving the fuel efficiency of automobiles has become an important issue. Therefore, there has been a growing movement to reduce the weight of automobile bodies by increasing the strength and thinning of steel sheets, which are the raw materials for automobile parts.
[0003] In addition, social demands for improved collision safety of automobiles are becoming stronger, and therefore there is a demand for the development of steel sheets that not only have high strength but also have excellent impact resistance properties when an automobile collides while traveling (hereinafter simply referred to as impact resistance properties).
[0004] As an example of a steel sheet that can be used as a material for such automobile parts, Patent Document 1 discloses a high-strength hot-dip galvanized steel sheet having a component composition containing, by mass%, 0.05 to 0.3% C, 0.01 to 2.5% Si, 0.5 to 3.5% Mn, 0.003 to 0.100%, 0.02% or less S, 0.010 to 1.5% Al, 0.007% or less N, with the balance being Fe and unavoidable impurities, and having a microstructure containing, by area ratio, 20 to 87% ferrite, 3 to 10% martensite and retained austenite in total, and 10 to 60% tempered martensite, and having excellent workability with a high TS-El balance, excellent stretch flangeability, and low YR.
[0005] Patent Document 2 also describes a high-strength hot-dip galvanized steel sheet having a thickness of 0.6 to 5.0 mm and a plating layer on the surface of the steel sheet, the steel sheet structure containing a ferrite phase with a volume fraction of 40 to 90% and a retained austenite phase with a volume fraction of 3 to 25%, the retained austenite phase having a solute carbon content of 0.70 to 1.00%, an average particle size of 2.0 μm or less, an average distance between particles of 0.1 to 5.0 μm, a thickness of a decarburized layer in the surface layer of the steel sheet of 0.01 to 10.0 μm, an average particle size of oxides contained in the surface layer of the steel sheet of 30 to 120 nm, and an average density of 1.0 × 10 12 pieces / m 2 The above also discloses a high-strength hot-dip galvanized steel sheet that has an average work hardening coefficient (n value) of 0.080 or more at 3 to 7% plastic deformation, has high ductility while maintaining a high strength of 900 MPa or more in maximum tensile strength, and has excellent mechanical cutting properties.
[0006] Patent Document 3 discloses a high-strength hot-dip galvanized steel sheet having excellent delayed fracture resistance, characterized in that it has, by volume fraction, 40 to 90% of a ferrite phase and 5% or less of a retained austenite phase, the proportion of unrecrystallized ferrite in the entire ferrite phase being 50% or less, the grain size ratio, which is the value obtained by dividing the average grain size in the rolling direction of the ferrite phase by the average grain size in the sheet width direction, is 0.75 to 1.33, the length ratio, which is the value obtained by dividing the average length in the rolling direction of hard structures dispersed in an island shape by the average length in the sheet width direction, is 0.75 to 1.33, and the average aspect ratio of inclusions is 5.0 or less. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 5256689 [Patent Document 2] Patent No. 5354135 [Patent Document 3] Patent No. 5352793 Summary of the Invention [Problem to be solved by the invention]
[0008] In recent years, the practical use of steel plates with a tensile strength (hereinafter also referred to as TS) of 780 MPa or more has been increasing for impact energy absorbing components of automobiles, such as front side members and rear side members.
[0009] That is, in order to increase the energy absorbed during impact (hereinafter also referred to as impact absorption energy), it is effective to improve the yield stress (hereinafter also referred to as YS). However, when the TS and YS of a steel sheet are increased, generally, the press formability, particularly properties such as ductility, hole expandability, and bendability, decrease. Therefore, when it is assumed that such a steel sheet with increased TS and YS is applied to the above-mentioned impact energy absorbing parts of automobiles, press forming becomes difficult, and the yield decreases due to variations during forming. In particular, the decrease in press formability at the end of the steel sheet leads to the occurrence of end cracks in the actual part.
[0010] Patent Document 1 discloses a high-strength hot-dip galvanized steel sheet that has improved ductility, which is the press formability inside the steel sheet, and stretch flangeability, which is the press formability at the ends of the steel sheet. However, it cannot be said that the bendability and energy absorption characteristics are sufficient.
[0011] Patent Document 2 discloses a high-strength hot-dip galvanized steel sheet in which the ductility is improved by the generation of retained austenite inside the steel sheet and the mechanical cutting characteristics are improved by the formation of a decarburized layer on the surface of the steel sheet. However, it cannot be said that the bendability and energy absorption characteristics are sufficient.
[0012] Patent Document 3 discloses a high-strength hot-dip galvanized steel sheet in which the main structure inside the steel sheet is soft ferrite and the amount of unrecrystallized ferrite is limited to a small amount to improve ductility, and delayed fracture resistance and its anisotropy are improved by forming a decarburized layer on the surface of the steel sheet. However, it cannot be said that the bendability and energy absorption characteristics are sufficient.
[0013] From the above, it cannot be said that the steel sheets disclosed in Patent Documents 1 to 3 have a TS of 1180 MPa or more, and also have a high YS, a high yield ratio YR, excellent press formability (bendability and ductility of the steel sheet), and excellent energy absorption properties.
[0014] The present invention has been made in consideration of the above problems, and has an object to provide a steel sheet having a tensile strength TS of 1180 MPa or more and less than 1470 MPa, and also having a high yield stress YS, a high yield ratio YR, excellent press formability (bendability and ductility of the steel sheet) and excellent energy absorption characteristics, together with an advantageous manufacturing method thereof. Another object of the present invention is to provide a member made of the above-mentioned steel plate and a method for manufacturing the same.
[0015] The steel sheet referred to here also includes zinc-plated steel sheet, and zinc-plated steel sheet refers to hot-dip galvanized steel sheet (hereinafter also referred to as GI), alloyed hot-dip galvanized steel sheet (hereinafter also referred to as GA), or electro-galvanized steel sheet (hereinafter also referred to as EG).
[0016] Here, the tensile strength TS is measured by a tensile test in accordance with JIS Z 2241 (2011).
[0017] Moreover, having a high yield stress YS, a high yield ratio YR, excellent press formability (bendability and ductility of the steel sheet), and excellent energy absorption characteristics means satisfying the following.
[0018] A high yield stress YS means that the YS measured in a tensile test conforming to JIS Z 2241 (2011) satisfies the following formula (A) or (B) depending on the TS measured in the tensile test. (A) When 1180MPa≦TS<1320MPa, 750MPa≦YS (B) When TS is 1320MPa or less, YS is 850MPa or less
[0019] In addition, a high yield ratio (YR) refers to a YR calculated based on the yield stress (YS) and tensile strength (TS) measured in a tensile test conforming to JIS Z 2241 (2011) of 0.70 or more.
[0020] In addition, excellent bendability refers to a bending angle (α) of 80° or more at maximum load measured in a bending test conforming to the VDA standard (VDA238-100) prescribed by the German Association of the Automotive Industry.
[0021] In addition, excellent ductility (excellent internal stretch formability of the steel sheet) means that the total elongation (El) measured in a tensile test conforming to JIS Z 2241 (2011) satisfies the following formula (A) or (B) depending on the TS measured in the tensile test. (A) When 1180MPa≦TS<1320MPa, 11.0%≦El (B) 1320MPa≦TS, 9.0%≦El
[0022] In addition to having a high YS, excellent energy absorption characteristics means that the integral value AE of the load-stroke curve at maximum load, measured in a bending test that complies with the VDA standard (VDA238-100) defined by the German Association of the Automotive Industry, is 70,000 N·mm or more. [Means for solving the problem]
[0023] The present inventors have conducted extensive research in order to achieve the above object. As a result, the composition of the steel sheet base material was properly adjusted, and the total area ratio of the structure other than ferrite was adjusted to S. A / 2 or less (S AWhen the soft surface layer is an area where the area ratio is the total area ratio of structures other than ferrite at the 1 / 4 position of the sheet thickness), the soft surface layer has a thickness of 20 μm or more from the surface of the base steel sheet in the sheet thickness direction, and the structure at the 1 / 4 position of the sheet thickness of the base steel sheet has an area ratio of ferrite: less than 20.0% (including 0.0%), a volume ratio of retained austenite: 3.0% to 15.0%, an area ratio of fresh martensite: 10.0% or less (including 0.0%), a total area ratio of bainitic ferrite and tempered martensite (excluding retained austenite): 45.0% to 90.0%, and the grain boundary length L F―MA and the grain boundary length of ferrite L F Regarding L F―MA / L F It was found that this makes it possible to obtain a steel sheet having a TS of 1180 MPa or more and less than 1470 MPa, high YS, high YR, excellent press formability (bendability and ductility of the steel sheet), and excellent energy absorption properties. The present invention has been completed based on the above findings and through further investigation.
[0024] That is, the gist and configuration of the present invention are as follows. [1] A steel plate having a base steel plate, the base steel plate comprising: In mass%, C: 0.050% or more and 0.400% or less, Si: 0.20% or more and 3.00% or less, Mn: 1.00% or more and less than 3.50% P: 0.001% or more and 0.100% or less, S: 0.0001% or more and 0.0200% or less, Al: 0.010% to 2.000% and N: 0.0100% or less and the balance being Fe and unavoidable impurities; The structure at 1 / 4 of the thickness of the base steel sheet is as follows: Ferrite area ratio: less than 20.0% (including 0.0%), Area ratio of retained austenite: 3.0% or more and 15.0% or less, Area ratio of fresh martensite: 10.0% or less (including 0.0%), Total area ratio of bainitic ferrite and tempered martensite: 45.0% or more and 90.0% or less; The grain boundary length L between the ferrite grain boundary and fresh martensite and / or retained austenite F―MA and the grain boundary length of ferrite L F Regarding L F―MA / L F : A steel structure that satisfies 0.70 or less, having Furthermore, the layer is formed to a thickness of 20 μm or more from the surface of the base steel sheet in the thickness direction. The steel structure has a surface soft layer in which the total area ratio of structures other than ferrite in the steel structure is 1 / 2 or less at a 1 / 4 position of the plate thickness, A steel plate having a tensile strength of 1180 MPa or more but less than 1470 MPa. [2] The composition further includes, in mass%, Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less Sb: 0.200% or less, Sn: 0.200% or less, Cu: 1.000% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co:0.0200% or less, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less and REM: 0.0200% or less The steel sheet according to the above [1], comprising at least one selected from the following: [3] The steel sheet according to [1] or [2] above, having a zinc-plated layer on one or both sides of the base steel sheet. [4] A member made using the steel plate according to any one of [1] to [3] above. [5] A hot rolling process in which a steel slab having the composition described in [1] or [2] is hot rolled to obtain a hot rolled steel sheet; A pickling process for pickling the hot-rolled steel sheet; An annealing process in which the steel sheet after the pickling process is heated and annealed under the conditions of an annealing temperature of 720°C to 860°C, a holding time of 20 seconds or more, and a dew point of -10°C or more; A rapid heating process of rapidly heating the annealing temperature to the annealing temperature + 10 ° C. or higher at a temperature increase rate of 10 ° C. / sec or higher; A cooling process in which the steel sheet after the rapid heating process is cooled to a cooling stop temperature of 100°C or more and 300°C or less; A reheating and holding process of heating the steel sheet after the cooling process to a tempering temperature of 460 ° C. or less and holding the tempering time in the temperature range of 10 seconds to 2000 seconds. Or even The method for producing a steel sheet includes a cold rolling step of cold rolling the steel sheet after the pickling step and before the annealing step at a rolling reduction of 20% or more and 80% or less to obtain a cold-rolled steel sheet. [6] The method for producing a steel sheet according to [5] above, wherein a threading speed LS (m / min) of the steel sheet in the annealing step satisfies the following formula (1): 3.0 / (t×W×4.716×10―4 ) <LS<390.0 / (t×W×4.716×10 ―4 )...Equation (1) Where: t: Plate thickness (mm) after pickling process and before annealing process, W: Sheet width after pickling and before annealing (mm) It is. [7] A hot-dip galvanizing step of immersing the steel sheet in a hot-dip galvanizing bath during the cooling step, after the cooling step and before the reheating and holding step, or after the reheating and holding step, to form a zinc-coated layer on the steel sheet, Alternatively, the method for producing a steel sheet according to the above [5] or [6] further comprises an alloying treatment step of subjecting the steel sheet on which the zinc plating layer has been formed to an alloying treatment. [8] The method for producing a steel sheet according to [5] or [6], further comprising, after the reheating and holding step, an electrogalvanizing step of immersing the steel sheet in an electrogalvanizing bath to form a zinc plating layer on the steel sheet. [9] A method for producing a component, comprising the step of subjecting the steel plate according to any one of [1] to [3] above to at least one of forming and joining to produce a component. Effect of the Invention
[0025] According to the present invention, a steel sheet can be obtained which has a tensile strength TS of 1180 MPa or more and less than 1470 MPa, as well as a high yield stress YS, a high yield ratio YR, excellent press formability (bendability and ductility of the steel sheet), and excellent energy absorption characteristics. Furthermore, members made from the steel plate of the present invention have high strength, high yield stress YS, high yield ratio YR, excellent press formability (bendability and ductility of the steel plate), and excellent energy absorption properties, and can be extremely advantageously used in automobile impact energy absorbing members, etc. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 shows examples of SEM microstructure images used for identifying the structure, where (a) is a microstructure image of Comparative Example No. 19, and (b) is a microstructure image of Invention Example No. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The present invention will be described based on the following embodiments.
[0028] [1. Steel plate] The steel sheet of the present invention is a steel sheet having a base steel sheet, the base steel sheet containing, by mass%, C: 0.050% or more and 0.400% or less, Si: 0.20% or more and 3.00% or less, Mn: 1.00% or more and less than 3.50%, P: 0.001% or more and 0.100% or less, S: 0.0001% or more and 0.0200% or less, Al: 0.010% or more and 2.000% or less, and N: 0.0100% or less, with the balance being Fe and unavoidable impurities, and As for the structure, the area ratio of ferrite is less than 20.0% (including 0.0%), the area ratio of retained austenite is 3.0% or more and 15.0% or less, the area ratio of fresh martensite is 10.0% or less (including 0.0%), the total area ratio of bainitic ferrite and tempered martensite is 45.0% or more and 90.0% or less, and the grain boundary length L F―MA and the grain boundary length of ferrite L F Regarding L F―MA / L F 0.70 or less, and further having a soft surface layer formed to a thickness of 20 μm or more from the surface of the base steel sheet in the sheet thickness direction, in which the total area ratio of structures other than ferrite in the steel structure is 1 / 2 or less at the 1 / 4 position in the sheet thickness, and having a tensile strength of 1,180 MPa or more and less than 1,470 MPa. The steel plate of the present invention has a tensile strength TS (hereinafter, tensile strength TS may be simply referred to as TS) of 1180 MPa or more and less than 1470 MPa, as well as a high yield stress YS (hereinafter, yield stress YS may be simply referred to as YS), a high yield ratio YR (hereinafter, yield ratio YR may be simply referred to as YR), excellent press formability (bendability and ductility of the steel plate), and excellent energy absorption characteristics. The steel sheet may have a zinc plating layer as the outermost layer on one or both sides of the steel sheet. The steel sheet having a zinc plating layer may be a zinc-plated steel sheet. More specifically, a steel sheet having a hot-dip galvanized layer among the zinc-coated layers may be referred to as a hot-dip galvanized steel sheet. Furthermore, a steel sheet having a galvannealed layer among the galvanized layers may be referred to as a galvannealed steel sheet. Furthermore, among the zinc-plated layers, the steel sheet having an electrolytic zinc-plated layer may be referred to as an electrolytic zinc-plated steel sheet.
[0029] Ingredient composition First, the composition of the base steel sheet of the steel sheet according to the embodiment of the present invention will be described. Note that the unit of the composition is always "mass %", but hereinafter, unless otherwise specified, it will be simply shown as "%".
[0030] C: 0.050% or more and 0.400% or less C is an effective element for generating appropriate amounts of fresh martensite, tempered martensite, bainitic ferrite, and retained austenite to ensure a TS of 1180 MPa or more and less than 1470 MPa and a high YS. If the C content is less than 0.050%, the area ratio of ferrite increases, making it difficult to achieve a TS of 1180 MPa or more. It also leads to a decrease in YS. On the other hand, if the C content exceeds 0.400%, the area ratio of fresh martensite increases excessively, making it difficult to make the TS less than 1470 MPa. In addition, the increase in fresh martensite may introduce mobile dislocations into ferrite and bainitic ferrite, resulting in a decrease in YR. Furthermore, since fresh martensite becomes the starting point for void generation during the VDA bending test, there is a risk that the desired bendability of the steel sheet may not be achieved. Therefore, the C content is set to 0.050% or more and 0.400% or less. The C content is preferably 0.100% or more. Moreover, the C content is preferably 0.300% or less.
[0031] Si: 0.20% or more and 3.00% or less Silicon inhibits the formation of carbides during cooling after annealing and promotes the formation of retained austenite. That is, silicon is an element that affects the area ratio of retained austenite. If the silicon content is less than 0.20%, the area ratio of retained austenite decreases, and ductility decreases. On the other hand, if the Si content exceeds 3.00%, the area ratio of ferrite increases excessively, which may result in a decrease in YS and a decrease in YR. Therefore, the Si content is set to 0.20% or more and 3.00% or less. The Si content is preferably 2.00% or less. Also, the Si content is preferably 0.50% or more.
[0032] Mn: 1.00% or more and less than 3.50% Mn is an element that adjusts the area ratio of bainitic ferrite, tempered martensite, etc. Here, if the Mn content is less than 1.00%, the area ratio of ferrite increases excessively, making it difficult to achieve a TS of 1180 MPa or more. In addition, this also leads to a decrease in YS. On the other hand, when the Mn content is 3.50% or more, the martensite transformation start temperature Ms (hereinafter also simply referred to as Ms point or Ms) decreases, and the martensite generated in the cooling process decreases. As a result, the martensite generated during final cooling increases, and the martensite generated at that time is not sufficiently tempered, and the area ratio of hard fresh martensite increases. The increase in fresh martensite may introduce mobile dislocations into ferrite and bainitic ferrite, decreasing YS. Furthermore, YR decreases. Furthermore, since fresh martensite becomes the starting point of void generation during the VDA bending test, there is a risk that the desired bendability of the steel sheet cannot be achieved. Therefore, the Mn content is set to 1.00% or more and less than 3.50%. The Mn content is preferably 2.00% or more. Also, the Mn content is preferably 3.00% or less.
[0033] P: 0.001% or more and 0.100% or less P is an element that has a solid solution strengthening effect and increases the TS and YS of a steel sheet. To obtain this effect, the P content is set to 0.001% or more. On the other hand, if the P content exceeds 0.100%, P segregates at the prior austenite grain boundaries and embrittles the grain boundaries, which increases the amount of voids generated during the VDA bending test, and there is a risk that the desired bendability cannot be achieved. Therefore, the P content is set to 0.001% or more and 0.100% or less, and preferably 0.030% or less.
[0034] S: 0.0001% or more and 0.0200% or less S exists as sulfides in steel. In particular, if the S content exceeds 0.0200%, the amount of voids generated during a VDA bending test increases, and there is a risk that the desired bendability cannot be achieved. Therefore, the S content is set to 0.0200% or less, preferably 0.0080% or less, and more preferably 0.0040% or less. Due to restrictions in production technology, the S content is set to 0.0001% or more, and preferably 0.0003% or more.
[0035] Al: 0.010% or more and 2.000% or less Al suppresses the formation of carbides during cooling after annealing and promotes the formation of retained austenite. In other words, Al is an element that affects the volume fraction of retained austenite. To obtain these effects, the Al content is set to 0.010% or more. On the other hand, if the Al content exceeds 2.000%, the area ratio of ferrite increases excessively, making it difficult to achieve a TS of 1180 MPa or more, and also resulting in a decrease in YS. Therefore, the Al content is set to 0.010% or more and 2.000% or less. The Al content is preferably 0.015% or more. The Al content is preferably 1.000% or less, and more preferably 0.100% or less.
[0036] N: 0.0100% or less N exists as nitrides in steel. In particular, if the N content exceeds 0.0100%, the amount of voids generated during a VDA bending test increases, and there is a risk that the desired bendability cannot be achieved. Therefore, the N content is set to 0.0100% or less, and preferably to 0.0050% or less. Although there is no particular lower limit for the N content, due to constraints on production technology, the N content is preferably 0.0005% or more, and more preferably 0.0010% or more.
[0037] The basic composition of the base steel sheet of the steel sheet according to one embodiment of the present invention has been described above, but the base steel sheet of the steel sheet according to one embodiment of the present invention has a composition that contains the basic components, with the balance other than the basic components including Fe (iron) and unavoidable impurities. Here, it is preferable that the base steel sheet of the steel sheet according to one embodiment of the present invention has a composition that contains the basic components, with the balance consisting of Fe and unavoidable impurities.
[0038] In addition to the basic components, the base steel sheet of the steel sheet according to one embodiment of the present invention may contain at least one selected from the optional components shown below. Note that the effects of the present invention can be obtained so long as the optional components shown below are contained in amounts not exceeding the upper limit amounts shown below, so no lower limit is particularly set. Note that when the optional elements shown below are contained in amounts less than the preferred lower limit values described below, the elements are considered to be contained as unavoidable impurities.
[0039] Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less, Sb: 0. 200% or less, Sn: 0.200% or less, Cu: 1.000% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co: 0.0200 %, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less, and at least one selected from REM: 0.0200% or less.
[0040] Nb: 0.200% or less Nb forms fine carbides, nitrides, or carbonitrides during hot rolling or annealing, thereby increasing TS and YS. To obtain such an effect, the Nb content is preferably 0.001% or more. The Nb content is more preferably 0.005% or more. On the other hand, if the Nb content exceeds 0.200%, a large amount of coarse precipitates and inclusions may be generated. In such a case, the amount of voids generated during the VDA bending test increases, and the desired bendability may not be achieved. Therefore, when Nb is contained, the Nb content is preferably 0.200% or less. The Nb content is more preferably 0.060% or less.
[0041] Ti: 0.200% or less Ti, like Nb, forms fine carbides, nitrides, or carbonitrides during hot rolling or annealing, thereby increasing TS and YS. To obtain such an effect, the Ti content is preferably 0.001% or more. The Ti content is more preferably 0.005% or more. On the other hand, if the Ti content exceeds 0.200%, a large amount of coarse precipitates and inclusions may be generated. In such a case, the amount of voids generated during the VDA bending test increases, and the desired bendability may not be achieved. Therefore, when Ti is contained, the Ti content is preferably 0.200% or less. The Ti content is more preferably 0.060% or less.
[0042] V:0.200% or less Like Nb and Ti, V forms fine carbides, nitrides, or carbonitrides during hot rolling or annealing, thereby increasing TS and YS. To obtain such an effect, the V content is preferably 0.001% or more. The V content is more preferably 0.005% or more. The V content is further preferably 0.010% or more, and even more preferably 0.030% or more. On the other hand, if the V content exceeds 0.200%, a large amount of coarse precipitates and inclusions may be generated. In such a case, the amount of voids generated during the VDA bending test increases, and the desired bendability may not be achieved. Therefore, when V is contained, the V content is preferably 0.200% or less. The V content is more preferably 0.060% or less.
[0043] B: 0.0100% or less B is an element that enhances hardenability by segregating at austenite grain boundaries. Also, B is an element that inhibits the formation and grain growth of ferrite during cooling after annealing. In order to obtain such effects, the B content is preferably 0.0001% or more. The B content is more preferably 0.0002% or more. The B content is further preferably 0.0005% or more, and even more preferably 0.0007% or more. On the other hand, if the B content exceeds 0.0100%, cracks may occur inside the steel sheet during hot rolling, and the amount of voids generated during the VDA bending test may increase, making it difficult to achieve the desired bendability. Therefore, when B is contained, the B content is preferably 0.0100% or less, and more preferably 0.0050% or less.
[0044] Cr:1.000% or less Since Cr is an element that enhances hardenability, the addition of Cr produces a large amount of tempered martensite, ensuring a TS of 1180 MPa or more and a high YS. To obtain such effects, the Cr content is preferably 0.0005% or more. The Cr content is more preferably 0.010% or more. The Cr content is further preferably 0.030% or more, and even more preferably 0.050% or more. On the other hand, if the Cr content exceeds 1.000%, the area ratio of hard fresh martensite increases excessively, and mobile dislocations are introduced into ferrite and bainitic ferrite, which may decrease the YS. Furthermore, since fresh martensite becomes the starting point for void generation during the VDA bending test, the desired bendability of the steel sheet may not be achieved. Therefore, when Cr is contained, the Cr content is preferably 1.000% or less. Moreover, the Cr content is more preferably 0.800% or less, even more preferably 0.700% or less, and even more preferably 0.200% or less.
[0045] Ni: 1.000% or less Since Ni is an element that enhances hardenability, the addition of Ni produces a large amount of tempered martensite, ensuring a TS of 1180 MPa or more and a high YS. To obtain such effects, the Ni content is preferably 0.005% or more. The Ni content is more preferably 0.020% or more. The Ni content is further preferably 0.040% or more, and even more preferably 0.060% or more. On the other hand, if the Ni content exceeds 1.000%, the area ratio of fresh martensite increases excessively, and mobile dislocations are introduced into ferrite and bainitic ferrite, which may decrease the YS. Furthermore, since fresh martensite becomes the starting point for void generation during the VDA bending test, the desired bendability of the steel sheet may not be achieved. Therefore, when Ni is contained, the Ni content is preferably 1.000% or less. The Ni content is more preferably 0.800% or less. Furthermore, the Ni content is more preferably 0.600% or less, and even more preferably 0.400% or less.
[0046] Mo: 1.000% or less Mo is an element that enhances hardenability, so the addition of Mo produces a large amount of tempered martensite, ensuring a TS of 1180 MPa or more and a high YS. To achieve this effect, the Mo content is preferably 0.010% or more. The Mo content is more preferably 0.030% or more. On the other hand, if the Mo content exceeds 1.000%, the area ratio of fresh martensite increases excessively, and mobile dislocations are introduced into ferrite and bainitic ferrite, which may decrease the YS. Furthermore, since fresh martensite becomes the origin of void generation during the VDA bending test, the desired bendability of the steel sheet may not be achieved. Therefore, when Mo is contained, the Mo content is preferably 1.000% or less. The Mo content is more preferably 0.500% or less, further preferably 0.450% or less, and further preferably 0.400% or less. The Mo content is more preferably 0.350% or less, and further more preferably 0.300% or less. The Mo content is more preferably 0.100% or less.
[0047] Sb: 0.200% or less Sb is an element that is effective in suppressing the diffusion of C near the steel sheet surface during annealing and controlling the formation of a soft layer near the steel sheet surface. If the soft layer increases excessively near the steel sheet surface, it becomes difficult to achieve a TS of 1180 MPa or more. It also leads to a decrease in YS. Therefore, the Sb content is preferably 0.002% or more. The Sb content is more preferably 0.005% or more. On the other hand, if the Sb content exceeds 0.200%, a soft layer is not formed near the steel sheet surface, which may result in a decrease in energy absorption properties. Therefore, when Sb is contained, the Sb content is preferably 0.200% or less. The Sb content is more preferably 0.020% or less.
[0048] Sn: 0.200% or less Like Sb, Sn is an element that is effective in suppressing the diffusion of C near the steel sheet surface during annealing and controlling the formation of a soft layer near the steel sheet surface. If the soft layer increases excessively near the steel sheet surface, it becomes difficult to achieve a TS of 1180 MPa or more. It also leads to a decrease in YS. Therefore, the Sn content is preferably 0.002% or more. The Sn content is more preferably 0.005% or more. On the other hand, if the Sn content exceeds 0.200%, a soft layer is not formed near the steel sheet surface, which may result in a decrease in energy absorption properties. Therefore, when Sn is contained, the Sn content is preferably 0.200% or less. The Sn content is more preferably 0.020% or less.
[0049] Cu:1.000% or less Since Cu is an element that enhances hardenability, the addition of Cu produces a large amount of tempered martensite, ensuring a TS of 1180 MPa or more and a high YS. To obtain such effects, the Cu content is preferably 0.005% or more. The Cu content is more preferably 0.008% or more, and even more preferably 0.010% or more. The Cu content is more preferably 0.020% or more, and even more preferably 0.050% or more. On the other hand, if the Cu content exceeds 1.000%, the area ratio of fresh martensite increases excessively, and a large amount of coarse precipitates and inclusions may be generated. In such a case, the fresh martensite and the coarse precipitates and inclusions become the starting points for void generation during the VDA bending test, so that the desired bendability of the steel sheet may not be achieved. In addition, the increase in the area ratio of fresh martensite may introduce mobile dislocations into ferrite and bainitic ferrite, which may decrease the YS. Therefore, when Cu is contained, the Cu content is preferably 1.000% or less. The Cu content is more preferably 0.200% or less.
[0050] Ta:0.100% or less Ta, like Ti, Nb and V, increases TS and YS by forming fine carbides, nitrides or carbonitrides during hot rolling or annealing. In addition, Ta partially dissolves in Nb carbides or Nb carbonitrides to generate composite precipitates such as (Nb,Ta)(C,N). This inhibits the coarsening of precipitates and stabilizes precipitation strengthening. This further improves TS and YS. To obtain such effects, the Ta content is preferably 0.001% or more. The Ta content is more preferably 0.002% or more, and even more preferably 0.004% or more. On the other hand, if the Ta content exceeds 0.100%, a large amount of coarse precipitates and inclusions may be generated. In such a case, the amount of voids generated during the VDA bending test increases, and the desired bendability may not be achieved. Therefore, when Ta is contained, the Ta content is preferably 0.100% or less. The Ta content is more preferably 0.090% or less, and even more preferably 0.080% or less. The Ta content is more preferably 0.020% or less.
[0051] W: 0.500% or less W is an element that enhances hardenability, so the addition of W produces a large amount of tempered martensite, ensuring a TS of 1180 MPa or more and a high YS. To achieve this effect, the W content is preferably 0.001% or more. The W content is more preferably 0.030% or more. On the other hand, if the W content exceeds 0.500%, the area ratio of hard fresh martensite increases excessively, and mobile dislocations are introduced into ferrite and bainitic ferrite, which may decrease the YS. Furthermore, since fresh martensite becomes the starting point for void generation during the VDA bending test, the desired bendability of the steel sheet may not be achieved. Therefore, when W is contained, the W content is preferably 0.500% or less. The W content is more preferably 0.450% or less, and even more preferably 0.400% or less. The W content is even more preferably 0.300% or less. The W content is even more preferably 0.100% or less.
[0052] Mg: 0.0200% or less Mg is an element that is effective in making the shape of inclusions such as sulfides and oxides spheroidal and improving the ultimate deformability and further the bendability of the steel sheet. To obtain such effects, the Mg content is preferably 0.0001% or more. The Mg content is more preferably 0.0005% or more, even more preferably 0.0010% or more, and even more preferably 0.0020% or more. On the other hand, if the Mg content exceeds 0.0200%, a large amount of coarse precipitates and inclusions may be generated. In such a case, the amount of voids generated during the VDA bending test increases, and the desired bendability may not be achieved. Therefore, when Mg is contained, the Mg content is preferably 0.0200% or less. The Mg content is more preferably 0.0180% or less, and further preferably 0.0150% or less.
[0053] Zn: 0.0200% or less Zn is an element that is effective in making the shape of inclusions spheroidal and improving the ultimate deformability and further the bendability of the steel sheet. To obtain such effects, the Zn content is preferably 0.0010% or more. The Zn content is more preferably 0.0020% or more, and even more preferably 0.0030% or more. On the other hand, if the Zn content exceeds 0.0200%, a large amount of coarse precipitates and inclusions may be generated. In such a case, the amount of voids generated during the VDA bending test may increase, and the desired bendability may not be achieved. Therefore, when Zn is contained, the Zn content is preferably 0.0200% or less. The Zn content is more preferably 0.0180% or less, and even more preferably 0.0150% or less.
[0054] Co:0.0200% or less Like Zn, Co is an element that is effective in making the shape of inclusions spheroidal and improving the ultimate deformability and further the bendability of the steel sheet. To obtain such effects, the Co content is preferably 0.0010% or more. The Co content is more preferably 0.0020% or more, and even more preferably 0.0030% or more. On the other hand, if the Co content exceeds 0.0200%, a large amount of coarse precipitates and inclusions may be generated. In such a case, the amount of voids generated during the VDA bending test may increase, and the desired bendability may not be achieved. Therefore, when Co is contained, the Co content is preferably 0.0200% or less. The Co content is more preferably 0.0180% or less, and further preferably 0.0150% or less.
[0055] Zr: 0.1000% or less Zr, like Zn and Co, is an element that is effective in making the shape of inclusions spheroidal and improving the ultimate deformability and further the bendability of the steel sheet. In order to obtain such effects, the Zr content is preferably 0.0010% or more. On the other hand, if the Zr content exceeds 0.1000%, a large amount of coarse precipitates and inclusions may be generated. In such a case, the amount of voids generated during the VDA bending test may increase, and the desired bendability may not be achieved. Therefore, when Zr is contained, the Zr content is preferably 0.1000% or less. The Zr content is more preferably 0.0300% or less, and further preferably 0.0100% or less.
[0056] Ca:0.0200% or less Ca exists as inclusions in steel. If the Ca content exceeds 0.0200%, a large amount of coarse inclusions may be generated. In such a case, the amount of voids generated during the VDA bending test increases, and the desired bendability may not be achieved. Therefore, when Ca is contained, the Ca content is preferably 0.0200% or less. The Ca content is preferably 0.0020% or less. Although there is no particular lower limit for the Ca content, the Ca content is preferably 0.0005% or more, and more preferably 0.0010% or more due to restrictions on production technology.
[0057] Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less, REM: 0.0200% or less Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi and REM are all elements effective for improving the ultimate deformability and further the bendability of steel sheets. In order to obtain such effects, it is preferable that the contents of Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi and REM are each 0.0001% or more. On the other hand, if the contents of Se, Te, Ge, Sr, Cs, Hf, Pb, Bi and REM exceed 0.0200% or the content of As exceeds 0.0500%, a large amount of coarse precipitates and inclusions may be generated. In such a case, the amount of voids generated during the VDA bending test increases, and the desired bendability may not be achieved. Therefore, when at least one of Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi, and REM is contained, it is preferable that the contents of Se, Te, Ge, As, Sr, Cs, Hf, Pb, Bi, and REM are each 0.0200% or less, and the As content is 0.0500% or less. The Se content is more preferably 0.0005% or more, and further preferably 0.0008% or more. The Se content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The Te content is more preferably 0.0005% or more, and further preferably 0.0008% or more. The Te content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The Ge content is more preferably 0.0005% or more, and further preferably 0.0008% or more. The Ge content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The As content is more preferably 0.0010% or more, and further preferably 0.0015% or more. The As content is more preferably 0.0400% or less, and further preferably 0.0300% or less. The Sr content is more preferably 0.0005% or more, and further preferably 0.0008% or more. The Sr content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The Cs content is more preferably 0.0005% or more, and further preferably 0.0008% or more. The Cs content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The Hf content is more preferably 0.0005% or more, and further preferably 0.0008% or more. The Hf content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The Pb content is more preferably 0.0005% or more, and further preferably 0.0008% or more. The Pb content is more preferably 0.0180% or less, and further preferably 0.0150% or less. The Bi content is more preferably 0.0005% or more, and further preferably 0.0008% or more. The Bi content is more preferably 0.0180% or less, further preferably 0.0150% or less, and even more preferably 0.0100% or less. The REM content is more preferably 0.0005% or more, and further preferably 0.0008% or more. The REM content is more preferably 0.0180% or less, and further preferably 0.0150% or less.
[0058] In the present invention, REM refers to scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanoids from lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. The REM content in the present invention is the total content of one or more elements selected from the above-mentioned REM. The REM is not particularly limited, but is preferably La and / or Ce.
[0059] That is, the base steel sheet of the steel sheet of the present invention contains, in mass%, C: 0.050% or more and 0.400% or less, Si: 0.20% or more and 3.00% or less, Mn: 1.00% or more and less than 3.50%, P: 0.001% or more and 0.100% or less, S: 0.0001% or more and 0.0200% or less, Al: 0.010% or more and 2.000% or less, and N: 0.0100% or less, and optionally Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Cu: 1.00 and at least one selected from among 0% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co: 0.0200% or less, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less and REM: 0.0200% or less, with the balance being Fe and unavoidable impurities.
[0060] steel structure Next, the steel structure of a steel sheet (base steel sheet) according to one embodiment of the present invention will be described. The structure at the 1 / 4 position of the sheet thickness of the base steel sheet is as follows: area ratio of ferrite: less than 20.0% (including 0.0%), area ratio of retained austenite: 3.0% to 15.0%, area ratio of fresh martensite: 10.0% or less (including 0.0%), total area ratio of bainitic ferrite and tempered martensite (excluding retained austenite): 45.0% to 90.0%, L F―MA / L F :0.70 or less.
[0061] Ferrite area ratio: Less than 20.0% (including 0.0%) Soft ferrite is a phase that improves ductility. However, the area ratio of ferrite increases excessively, and it may be difficult to achieve TS of 1180 MPa or more. It may also lead to a decrease in YR. Therefore, the area ratio of ferrite is less than 20.0%. The area ratio of ferrite is preferably 15.0% or less. The lower limit of the area ratio of ferrite is not particularly limited and may be 0.0%.
[0062] Area ratio of retained austenite: 3.0% to 15.0% In order to obtain good ductility, the area ratio of the retained austenite is set to 3.0% or more, and preferably 3.5% or more. On the other hand, if the area ratio of the retained austenite increases excessively, the carbon content in the retained austenite decreases and becomes unstable. In that case, the desired YS cannot be achieved. Therefore, the area ratio of the retained austenite is set to 15.0% or less. The area ratio of the retained austenite is preferably 12.0% or less, and more preferably 10.0% or less.
[0063] Area ratio of fresh martensite: 10.0% or less (including 0.0%) If the area ratio of fresh martensite is excessively increased, mobile dislocations are introduced into ferrite or bainitic ferrite, and the desired YS may not be achieved. In addition, the desired YR may not be obtained. In addition, since fresh martensite becomes the starting point for void generation during VDA bending test, the desired bendability of the steel sheet may not be achieved. In order to ensure high YS and good bendability of the steel sheet, the area ratio of fresh martensite is 10.0% or less, preferably 5.0% or less. The lower limit of the area ratio of fresh martensite is not particularly limited and may be 0.0%. It should be noted that fresh martensite is martensite that has been quenched (not tempered).
[0064] Total area ratio of bainitic ferrite and tempered martensite: 45.0% to 90.0% Bainitic ferrite and tempered martensite have intermediate hardness between soft ferrite and hard fresh martensite, and are important phases for ensuring good bendability of steel sheets. Bainitic ferrite is also a useful phase for obtaining an appropriate amount of retained austenite by utilizing the diffusion of C from bainitic ferrite to untransformed austenite. Tempered martensite is effective for improving TS and YS. Therefore, the total area ratio of bainitic ferrite and tempered martensite is set to 45.0% or more. It is preferably 50.0% or more. On the other hand, if the total area ratio of bainitic ferrite and tempered martensite is excessively increased, ductility decreases. Therefore, the total area ratio of bainitic ferrite and tempered martensite is set to 90.0% or less. The total area ratio of bainitic ferrite and tempered martensite is preferably 85.0% or less. Bainitic ferrite is upper bainite with little carbide that is formed in a relatively high temperature range.
[0065] L F―MA / L F : 0.70 or less The steel structure of the base steel sheet of the steel sheet according to one embodiment of the present invention further comprises L F―MA / L F :0.70 or less. Where: L F―MA : Length of grain boundary on ferrite grain boundary in contact with MA structure (fresh martensite and / or retained austenite) L F : Length of ferrite grain boundary In addition, L F―MA and L F is the grain boundary length measured in the same units. In the steel plate having a dual-phase structure according to an embodiment of the present invention, the presence of fresh martensite introduces mobile dislocations into the ferrite, making the ferrite more susceptible to yielding and decreasing the YS. F―MA / L F If L exceeds 0.70, the desired YS may not be achieved. Also, the desired YR may not be obtained. F―MA / L F The value must be 0.70 or less. F―MA / L F is preferably 0.68 or less, more preferably 0.65 or less. F―MA / L F The lower limit is not particularly limited, and may be 0.00. L F―MA / L F In order to make the Mn content of the steel less than 0.70, for example, the temperature is raised from the annealing temperature at a rate of 10°C / sec or more in the rapid heating step described below, whereby austenite can be generated around the ferrite by the diffusion of C alone. S The austenite has a high melting point and becomes bainitic ferrite or martensite during cooling. The martensite becomes tempered martensite during the reheating and holding process. In other words, a structure other than the hard phase (hard second phase) is generated from the austenite generated only by the diffusion of C.
[0066] The area ratio of the remaining structure other than the above is preferably 10.0% or less. The area ratio of the remaining structure is more preferably 5.0% or less. The area ratio of the remaining structure may be 0.0%. The remaining structure is not particularly limited, and examples thereof include carbides such as lower bainite, pearlite, and cementite. The type of the remaining structure can be confirmed, for example, by observation with a SEM (Scanning Electron Microscope).
[0067] Soft surface layer: The total area ratio of structures other than ferrite is 1 / 2 or less at the 1 / 4 position of the plate thickness. The base steel sheet of the steel sheet according to one embodiment of the present invention has a soft surface layer on the surface of the base steel sheet. The soft surface layer contributes to suppressing the progression of bending cracks during press forming and during vehicle collisions, thereby improving the bendability and energy absorption characteristics of the steel sheet. The soft surface layer means the decarburized layer, and the total area ratio of the structures other than ferrite in the cross section at the 1 / 4 position of the plate thickness is S A When the total area ratio of structures other than ferrite is S A This refers to the surface area where the surface area is less than 1 / 2. Here, the soft surface layer is formed in a region 20 μm or more from the surface of the base steel sheet in the sheet thickness direction. The region in which the soft surface layer is formed is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 120 μm or less from the surface of the base steel sheet in the sheet thickness direction. The thickness of the soft surface layer is preferably 25 μm or more, and more preferably 30 μm or more. In addition, the total area ratio S of the structures other than ferrite mentioned above A The 1 / 4 sheet thickness position of the steel sheet where the measurement is performed is a non-surface soft layer (a layer that does not satisfy the conditions of the surface soft layer defined in the present invention). It is.
[0068] Here, the area ratios of ferrite, bainitic ferrite, tempered martensite and hard phase (hard second phase (retained austenite + fresh martensite)) at the 1 / 4 sheet thickness position of the base steel sheet are measured as follows. That is, a sample is cut out from the base steel sheet so that the cross section of the sheet thickness parallel to the rolling direction of the base steel sheet becomes the observation surface. The observation surface of the sample is then mirror-polished using diamond paste. The observation surface of the sample is then finish-polished using colloidal silica, and etched with 3 vol.% nital to reveal the structure. Then, using a SEM (Scanning Electron Microscope), images are taken of three fields of view of 25.6 μm x 17.6 μm at the outermost layer position and 1 / 4 of the plate thickness position of the observation surface of the sample under conditions of an acceleration voltage of 15 kV and a magnification of 5000 times. From the obtained structural image (see FIG. 1), ferrite F, bainitic ferrite BF, tempered martensite TM, and hard phase H (hard second phase (retained austenite + fresh martensite)) are identified as follows.
[0069] Ferrite: A black region that is lumpy in shape. It contains almost no iron-based carbides. However, if it does contain iron-based carbides, the area of the ferrite includes the area of the iron-based carbides. The same applies to bainitic ferrite and tempered martensite, which will be described later. Bainitic ferrite: This is a region that is black to dark gray in color and has a massive or amorphous shape. It also contains no iron carbides or contains a relatively small amount of them. Tempered martensite: This is a gray area with an amorphous shape. It also contains a relatively large number of iron-based carbides. Hard phase (hard second phase (retained austenite + fresh martensite)): This is a region that is white to light gray in color and has an amorphous form. It does not contain iron-based carbides. If the size is relatively large, the color gradually darkens as it moves away from the interface with other structures, and the interior may be dark gray. Carbides: White areas that are dot-like or linear in shape. They are included in tempered martensite, bainitic ferrite, and ferrite. Remaining structure: Lower bainite, pearlite, internal oxides, etc., and the morphology thereof is as known.
[0070] Next, the areas of each phase identified in the structural image are color-coded (four-value image) using Adobe Photoshop by Adobe Systems, and the area of each phase is calculated. The area of each phase (total area of each phase) is divided by the area of the observation region (25.6 μm × 17.6 μm) and multiplied by 100 to calculate the value for three fields of view. The average value of these values is then determined as the area ratio of each phase (ferrite, bainitic ferrite, tempered martensite, and hard second phase).
[0071] The area ratio of retained austenite is measured as follows. The base steel plate is mechanically ground in the plate thickness direction (depth direction) to a position that is 1 / 4 of the plate thickness, and then chemically polished with oxalic acid to obtain the observation surface. The observation surface is then observed by X-ray diffraction. MoKα rays are used as the incident X-rays, and the ratio of the diffraction intensity of the (200), (211), and (220) faces of the fcc iron (austenite) to the diffraction intensity of the (200), (220), and (311) faces of the bcc iron is calculated, and the volume fraction of the retained austenite is calculated from the ratio of the diffraction intensity of each face. The retained austenite is then considered to be three-dimensionally homogeneous, and the volume fraction of the retained austenite is taken as the area fraction of the retained austenite.
[0072] The area ratio of fresh martensite is determined by subtracting the area ratio of retained austenite from the area ratio of the hard phase (hard second phase) determined as described above. [Area ratio of fresh martensite (%)] = [Area ratio of hard second phase (%)] - [Area ratio of retained austenite (%)]
[0073] The area ratio of the remaining structure is determined by subtracting the area ratio of ferrite, the area ratio of bainitic ferrite, the area ratio of tempered martensite, and the area ratio of the hard phase (hard second phase) determined as described above from 100.0%. [Area ratio of remaining structure (%)] = 100.0 - [Area ratio of ferrite (%)] - [Area ratio of bainitic ferrite (%)] - [Area ratio of tempered martensite (%)] - [Area ratio of hard second phase (%)]
[0074] For the measurement of the structure of the soft surface layer, if a zinc-coated layer is formed on the steel sheet, first peel off the zinc-coated layer, and measure the structure in the same way as at the 1 / 4 position in the sheet thickness direction at 1 μm intervals from the surface of the base steel sheet in the sheet thickness direction to a position 100 μm in the sheet thickness direction. After that, measurements are made at 20 μm intervals up to the center of the sheet thickness.
[0075] Also, L F―MA , L F is measured as follows: In the structural image (see, for example, Figure 1), ferrite and hard phases (hard second phases) are identified as described above. Then, the ferrite and hard phases (hard second phases) are manually extracted, and the L F―MA , L F We ask for the following respectively. Specifically, the ferrite grain boundary L was extracted using the quaternary structure image described above and the object function of Adobe Illustrator. F The curve along the grain boundary L, which is in contact with the ferrite and martensite structures (MA structure: fresh martensite + retained austenite), F―MA Draw a curve along each line and measure the length of the curve. F―MA L F Calculate the average value of L F―MA / L F Let us assume that.
[0076] Next, the mechanical properties of the steel plate according to one embodiment of the present invention will be described.
[0077] Tensile strength (TS): 1180MPa or more, less than 1470MPa The tensile strength TS of the steel plate according to one embodiment of the present invention is 1180 MPa or more and less than 1470 MPa. The yield stress (YS), yield ratio (YR), total elongation (El), bendability and energy absorption characteristics of the steel plate according to one embodiment of the present invention are as described above.
[0078] The tensile strength (TS), yield stress (YS), yield ratio (YR) and total elongation (El) are measured by a tensile test in accordance with JIS Z 2241 (2011) described later in the examples. The bendability and energy absorption properties of the steel sheet are measured by a VDA bending test described later in the examples.
[0079] Zinc plating layer A steel sheet according to one embodiment of the present invention may have a zinc-plated layer formed on a base steel sheet, and this zinc-plated layer may be provided on only one surface of the base steel sheet, or on both surfaces.
[0080] The galvanized layer referred to here refers to a plated layer containing Zn as a main component (Zn content: 50.0 mass % or more), and examples thereof include a hot-dip galvanized layer, a galvannealed hot-dip galvanized layer, and an electrolytic galvanized layer.
[0081] Here, the hot-dip galvanized layer is preferably composed of, for example, Zn, 20.0 mass% or less of Fe, and 0.001 mass% to 1.0 mass% or less of Al. The hot-dip galvanized layer may optionally contain one or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM in a total amount of 0.0 mass% to 3.5 mass%. The Fe content of the hot-dip galvanized layer is more preferably less than 7.0 mass%. The remainder other than the above elements is unavoidable impurities.
[0082] In addition, the galvannealed layer is preferably composed of, for example, Zn, 20% by mass or less of Fe, and 0.001% by mass or more and 1.0% by mass or less of Al. In addition, the galvannealed layer may optionally contain one or more elements selected from the group consisting of Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM in a total amount of 0.0% by mass or more and 3.5% by mass or less. The Fe content of the galvannealed layer is more preferably 7.0% by mass or more, and more preferably 8.0% by mass or more. The Fe content of the galvannealed layer is more preferably 15.0% by mass or less, and more preferably 12.0% by mass or less. The remainder other than the above elements is unavoidable impurities.
[0083] The electrolytic zinc plating layer is preferably composed of, for example, Zn and 9.0 mass % to 25.0 mass % Ni, the remainder being unavoidable impurities other than the above elements.
[0084] In addition, the coating weight of the hot-dip galvanized layer and the galvannealed hot-dip galvanized layer per side is not particularly limited, but is preferably 20 g / m 2 The coating weight of the hot-dip galvanized layer and the galvannealed hot-dip galvanized layer on one side is preferably 80 g / m or more. 2 The plating weight of the electrolytic zinc plating layer on one side is not particularly limited, but is preferably 10 g / m 2 The plating weight of the electrolytic zinc plating layer on one side is preferably 100 g / m or more. 2 It is preferable that:
[0085] The coating weight of the zinc-plated layer (hot-dip galvanized layer, alloyed hot-dip galvanized layer, electrolytic zinc-plated layer) is measured as follows. That is, a treatment solution is prepared by adding 0.6 g of a corrosion inhibitor for Fe (Ivit 700BK (registered trademark) manufactured by Asahi Chemical Industry Co., Ltd.) to 1 L of a 10 mass % aqueous hydrochloric acid solution. Next, a steel sheet to be used as a test material is immersed in the treatment solution to dissolve the zinc plating layer. The amount of mass loss of the test material before and after dissolution is then measured, and this value is divided by the surface area of the base steel sheet (the surface area of the part that was covered with plating) to obtain the plating coverage (g / m 2 ) is calculated.
[0086] The thickness of the steel plate according to one embodiment of the present invention is not particularly limited, but is preferably more than 0.8 mm, more preferably 0.9 mm or more, further preferably 1.0 mm or more, and most preferably 1.2 mm or more. The thickness of the steel plate is preferably 3.5 mm or less, and more preferably 2.3 mm or less. The width of the steel plate of the present invention is not particularly limited, but is preferably 500 mm or more, more preferably 750 mm or more, and is preferably 1600 mm or less, more preferably 1450 mm or less.
[0087] [2. Steel plate manufacturing method] Next, a method for manufacturing a steel sheet according to one embodiment of the present invention will be described.
[0088] A method for producing a steel sheet according to an embodiment of the present invention includes a hot rolling process in which a steel slab having the above-mentioned composition is hot-rolled to produce a hot-rolled steel sheet, a pickling process in which the hot-rolled steel sheet is pickled, an annealing process in which the steel sheet after the pickling process or the steel sheet after the cold rolling process is heated and annealed under conditions of an annealing temperature of 720°C to 860°C, a holding time of 20 seconds or more, and a dew point of -10°C or more, and a rapid heating process in which the temperature is raised from the annealing temperature to annealing temperature +10°C or higher under conditions of a heating rate of 10°C / second or more. the steel sheet after the rapid heating step is heated to a cooling stop temperature of 100°C or more and 300°C or less; and the reheating and holding step of heating the steel sheet after the cooling step to a tempering temperature of 460°C or less and holding the steel sheet in the above temperature range for a tempering time of 10 seconds or more and 2000 seconds or less, or further including a cold rolling step of cold rolling the steel sheet after the pickling step and before the annealing step with a reduction ratio of 20% or more and 80% or less to obtain a cold rolled steel sheet. It is preferable that the steel sheet passing speed LS (m / min) in the annealing process satisfies the following formula (1). 3.0 / (t×W×4.716×10 ―4 ) <LS<390.0 / (t×W×4.716×10 ―4 )...Equation (1) t: sheet thickness (mm) after pickling process and before annealing process, W: sheet thickness (mm) after pickling process and before annealing process. Unless otherwise specified, the above temperatures refer to the surface temperatures of the steel slab and the steel plate.
[0089] First, a steel slab having the above-mentioned composition is prepared. For example, a steel material is melted to obtain molten steel having the above-mentioned composition. The melting method is not particularly limited, and known melting methods such as converter melting and electric furnace melting can be used. The obtained molten steel is then solidified to obtain a steel slab. The method for obtaining a steel slab from molten steel is not particularly limited, and for example, a continuous casting method, an ingot casting method, or a thin slab casting method can be used. From the viewpoint of preventing macrosegregation, it is preferable to adopt a continuous casting method as a method for obtaining a steel slab from molten steel.
[0090] (Hot rolling process) Next, in the hot rolling process, the steel slab is hot rolled to produce a hot rolled steel sheet. The hot rolling may be performed by applying an energy-saving process, such as direct rolling (a method in which a steel slab is not cooled to room temperature, but is charged as a hot piece into a heating furnace and hot rolled), direct rolling (a method in which a steel slab is briefly kept at a certain temperature and then immediately rolled), etc.
[0091] The hot rolling conditions are not particularly limited, and the hot rolling can be performed, for example, under the following conditions. That is, the steel slab is once cooled to room temperature, and then reheated and rolled. The slab heating temperature (reheating temperature) is preferably 1100°C or higher from the viewpoints of dissolving carbides and reducing the rolling load. In addition, in order to prevent an increase in scale loss, the slab heating temperature is preferably 1300°C or lower. The slab heating temperature is based on the temperature of the steel slab surface.
[0092] Next, the steel slab is subjected to rough rolling according to a conventional method to obtain a rough rolled plate (hereinafter also referred to as a sheet bar). Next, the sheet bar is subjected to finish rolling to obtain a hot rolled steel plate. In addition, when the slab heating temperature is set low, it is preferable to heat the sheet bar using a bar heater or the like before the finish rolling in order to prevent problems during the finish rolling. In order to reduce the rolling load, the finish rolling temperature is preferably set to 800°C or higher. In addition, if the rolling reduction rate in the non-recrystallized state of austenite becomes high, an abnormal structure elongated in the rolling direction may develop, which may reduce the workability of the annealed sheet. Furthermore, by setting the finish rolling temperature to 800°C or higher, the steel structure at the hot rolled steel plate stage and, in turn, the steel structure of the final product are likely to become uniform. In addition, if the steel structure becomes non-uniform, the bendability tends to decrease. On the other hand, if the finish rolling temperature exceeds 950°C, the amount of oxide (scale) generated increases. As a result, the interface between the base steel and the oxide becomes rough, which may deteriorate the surface quality of the steel sheet after pickling and cold rolling. In addition, the crystal grains may become coarse, which may cause a decrease in the strength and bendability of the steel sheet. Therefore, it is preferable that the finish rolling temperature is in the range of 950°C or less. For the above reasons, it is preferable that the finish rolling temperature is in the range of 800°C or more and 950°C or less.
[0093] After the finish rolling, the hot-rolled steel sheet is coiled at a coiling temperature of preferably 450° C. or higher and preferably 750° C. or lower.
[0094] In addition, the sheet bars may be joined together during hot rolling and continuous finish rolling may be performed. Also, the sheet bars may be wound once before the finish rolling. In order to reduce the rolling load during hot rolling, a part or all of the finish rolling may be lubricated rolling. Performing lubricated rolling is also effective from the viewpoint of uniformity of the steel sheet shape and material quality. In addition, the friction coefficient during lubricated rolling is preferably in the range of 0.10 to 0.25. In the hot rolling process, which includes rough rolling and finish rolling, steel slabs are generally made into sheet bars by rough rolling and then into hot rolled steel sheets by finish rolling. However, depending on the mill capacity, etc., such divisions do not matter as long as the specified size is achieved.
[0095] (pickling process) The hot-rolled steel sheet after the hot rolling process is pickled. Pickling can remove oxides from the steel sheet surface, ensuring good chemical conversion treatment properties and plating quality. Pickling may be performed once or multiple times. There are no particular limitations on the pickling conditions, and the usual methods may be followed.
[0096] (Cold rolling process) Next, the hot-rolled steel sheet is cold-rolled as necessary to obtain a cold-rolled steel sheet. The cold rolling is performed by multi-pass rolling requiring two or more passes, such as tandem multi-stand rolling or reverse rolling. The cold rolling reduction (cumulative reduction) is not particularly limited, but is preferably 20% or more. The cold rolling reduction is preferably 80% or less. If the cold rolling reduction is less than 20%, the steel structure is likely to become coarse and non-uniform in the annealing process, and the TS and bendability of the final product may decrease. On the other hand, if the cold rolling reduction exceeds 80%, the steel sheet is likely to have a defective shape and the amount of zinc coating may become non-uniform. Furthermore, the cold-rolled steel sheet obtained after cold rolling may be optionally subjected to pickling.
[0097] (Annealing process) Next, in one embodiment of the present invention, after the pickling process (after the cold rolling process if cold rolling is performed), the steel sheet obtained as described above is heated and annealed at an annealing temperature of 720°C to 860°C and a holding time (annealing time) of 20 seconds or more. The number of annealing steps may be two or more, but one time is preferable from the viewpoint of energy efficiency. The annealing step is a step including the heating treatment and the soaking treatment.
[0098] Annealing temperature: 720℃ to 860℃ When the annealing temperature is less than 720°C, the rate of austenite formation during heating in the two-phase region of ferrite and austenite becomes insufficient. As a result, the area ratio of ferrite increases excessively after annealing, and YS decreases. In addition, the amount of fresh martensite increases due to excessive carbon concentration in austenite during annealing, and L F―MA / L F If the bending strength exceeds 0.70, the desired YS cannot be achieved, and the bendability of the steel sheet may not be achieved. Furthermore, it becomes difficult to achieve a TS of 1180 MPa or more. On the other hand, if the annealing temperature exceeds 860°C, the proportion of ferrite during annealing becomes insufficient, the diffusion of C in the vicinity of the steel sheet surface is suppressed, and the desired soft surface layer is not formed. Therefore, the annealing temperature is set to 720°C or higher and 860°C or lower. The annealing temperature is preferably 850°C or lower. The annealing temperature is the maximum temperature reached in the annealing process.
[0099] Holding time (annealing time): 20 seconds or more If the holding time (annealing time) is less than 20 seconds, the rate of austenite generation during heating in the two-phase region of ferrite and austenite becomes insufficient. As a result, the area ratio of ferrite increases excessively after annealing, which may result in a decrease in YS. Also, the YR decreases. In addition, the amount of fresh martensite increases due to the excessive concentration of carbon in the austenite during annealing, and the L F―MA / L F If the annealing time exceeds 0.70, the desired YS may not be obtained. In addition, the YR decreases. Furthermore, the bendability of the steel sheet may not be achieved. Furthermore, it becomes difficult to achieve a TS of 1180 MPa or more. Therefore, the holding time (annealing time) is set to 20 seconds or more. The holding time is preferably 30 seconds or more, and more preferably 50 seconds or more. Although there is no particular upper limit to the retention time, the retention time is preferably 900 seconds or less, and more preferably 800 seconds or less. The holding time is the holding time in the temperature range of (annealing temperature -40°C) or more and (annealing temperature) or less. In other words, the holding time includes not only the holding time at the annealing temperature, but also the residence time in the temperature range of (annealing temperature -40°C) or more and (annealing temperature) or less during heating and cooling before and after reaching the annealing temperature.
[0100] Dew point of the annealing process atmosphere (annealing atmosphere): -10℃ or higher In one embodiment of the present invention, the dew point of the atmosphere in the annealing step (annealing atmosphere) is set to -10°C or higher. By performing annealing in the annealing step with a dew point of the annealing atmosphere of -10°C or higher, the decarburization reaction is promoted and a surface soft layer having a desired thickness can be formed. The dew point of the annealing atmosphere in the annealing step is preferably -5°C or higher, more preferably 0°C or higher, and even more preferably more than 5°C. Although there is no particular upper limit for the dew point of the annealing atmosphere in the annealing step, in order to improve the plating adhesion when a zinc plating layer is formed, the dew point of the annealing atmosphere in the annealing step is preferably 30° C. or lower.
[0101] 3.0 / (t×W×4.716×10―4 ) <LS<390.0 / (t×W×4.716×10 ―4 )...Equation (1) In the present invention, from the viewpoint of production efficiency, it is preferable that the steel sheet threading speed LS (m / min) in the annealing process satisfies formula (1). In formula (1), t: plate thickness (mm) after pickling process and before annealing process, W: Sheet width after pickling and before annealing (mm), It is. The above production efficiency can be expressed as E by the following equation (2). E(ton / h)=LS×t×W×ρ×60×10 ―6 ...Equation (2) In formula (2), t: plate thickness (mm), W: Board width (mm), ρ: specific gravity of iron (ton / m 3 ), and ρ = 7.86 (ton / m 3 ),. In this case, E is preferably more than 3.0 ton / h and less than 390.0 ton / h. Based on this equation (2), the above equation (1) can be derived. If E is 3.0 ton / h or less, a soft surface layer is excessively formed during annealing, which may make it difficult to achieve a TS of 1180 MPa or more, and may also result in a decrease in YS. On the other hand, if E is 390.0 ton / h or more, it becomes difficult to form a desired soft surface layer during annealing, and the bendability of the steel sheet may not be achieved. Therefore, E is preferably more than 3.0 ton / h and less than 390.0 ton / h. Moreover, E is more preferably 16.0 ton / h or more, and more preferably 190.0 ton / h or less. From the above, LS (m / min) is 3.0 / (t×W×4.716×10 ―4 ) or more. LS (m / min) is 16.0 / (t×W×4.716×10 ―4 ) or more is more preferable. In addition, LS (m / min) is 390.0 / (t×W×4.716×10 ―4 ) is preferable. LS (m / min) is 190.0 / (t×W×4.716×10 ―4 ) or less is more preferable.
[0102] The sheet passing speed LS (m / min) is calculated by dividing the distance (m) traveled by the steel sheet in the annealing process by the time (min) required for the steel sheet to be transported in the annealing process.
[0103] A radiant tube furnace is generally used as the heat treatment furnace for the annealing process. The annealing temperature is obtained by a thermometer that measures the surface temperature of the steel sheet. The method of temperature measurement is not particularly limited, but for example, a radiation thermometer that measures the temperature by sensing infrared rays emitted by the steel sheet is suitable. In the case of a radiation thermometer, since it may be affected by reflected light of infrared rays emitted by the surrounding furnace body, a cover may be provided between the measurement part of the radiation thermometer and the detection part of the steel sheet. In addition, since it may be affected by the emissivity of the steel sheet surface, a multiple reflection type measurement method using a wedge-shaped space between the transport roll in the furnace and the steel sheet may be adopted.
[0104] (Rapid heating process) In one embodiment of the present invention, after the annealing step, the steel sheet obtained as described above is rapidly heated from the annealing temperature to the annealing temperature +10°C or higher at a heating rate of 10°C / sec or higher. When annealing is performed two or more times in the above-mentioned annealing step, the treatment in the rapid heating step performed after the annealing may also be performed two or more times, but the treatment in the rapid heating step may be performed only once.
[0105] Heating rate: 10℃ / sec or more In one embodiment of the present invention, the rate of temperature rise from the annealing temperature to the temperature reached in the rapid heating step described below is 10° C. / sec or more. By increasing the heating rate to 10°C / sec or more, the diffusion of Mn from ferrite to austenite is suppressed, and austenite can be generated only by the diffusion of C.S The temperature rise rate is high, and the material becomes bainitic ferrite or martensite during cooling. The martensite becomes tempered martensite during the reheating and holding process. In other words, by increasing the heating rate to 10°C / sec or more, the L F―MA / L F can be made 0.70 or less, and YS can be improved. YR can also be improved. Furthermore, production efficiency can be improved. Therefore, the heating rate from the annealing temperature to the rapid heating step temperature is set to 10°C / sec or more. The heating rate is more preferably 30°C / sec or more. On the other hand, if the heating rate exceeds 300°C / sec, there is a concern that the steel sheet may buckle due to thermal stress, and local high temperature areas may occur in the sheet width direction, making it difficult to maintain uniformity. Therefore, the heating rate in the rapid heating step is preferably 300°C / sec or less, and more preferably 150°C / sec or less.
[0106] Rapid heating process temperature: Annealing temperature + 10℃ or more If the temperature reached in the rapid heating process is less than the annealing temperature + 10°C, the formation of austenite is insufficient by the diffusion of C alone, and L F―MA / L F If the temperature exceeds 0.70, YS may decrease. Also, YR decreases. Therefore, the temperature reached in the rapid heating process is set to the annealing temperature +10°C or more. The temperature reached in the rapid heating step is preferably the annealing temperature +30° C. or more, and more preferably the annealing temperature +40° C. or more. There is no particular upper limit to the temperature reached in the rapid heating step, but from the viewpoint of production efficiency, it is preferably less than the annealing temperature + 100°C, and more preferably not more than the annealing temperature + 90°C.
[0107] The induction heating (IH) device in the rapid heating process adjusts the output to rapidly heat the steel sheet so that the temperature of the steel sheet is within the annealing temperature +10°C or more (preferably, 740°C or more and 940°C or less). When heating in such a temperature range, it is preferable that the induction heating (IH) device is of the transverse type. The appropriate rapid heating temperature varies depending on the chemical composition of the steel sheet. Therefore, it is preferable that the suitable temperature range is predicted in advance by measurement, calculation or simulation, and set taking into consideration the temperature of the steel sheet in the annealing process. The temperature reached in the rapid heating process can be measured by a thermometer that measures the surface temperature of the steel sheet. The method of temperature measurement is not particularly limited, but for example, a radiation thermometer that measures the temperature by sensing infrared rays emitted by the steel sheet is suitable. In the case of a radiation thermometer, since it may be affected by reflected light of infrared rays emitted by the surrounding furnace body, a cover may be provided between the measurement part of the radiation thermometer and the detection part of the steel sheet. In addition, since it may be affected by the emissivity of the steel sheet surface, a multiple reflection type measurement method using a wedge-shaped space between the transport roll in the furnace and the steel sheet may be adopted. In addition, it is preferable to use a scanning radiation thermometer to measure the temperature at each position in the width direction of the steel sheet.
[0108] (Holding process (preferable condition)) After the rapid heating step and before the cooling step, if necessary, a holding step may be performed in which the steel sheet is held in a temperature range of 400°C or more and 600°C or less (hereinafter also referred to as the holding temperature range) for less than 80 seconds.
[0109] Holding time in holding temperature range: Less than 80 seconds In the holding step, bainitic ferrite is generated, and C diffuses from the generated bainitic ferrite to the untransformed austenite adjacent to the bainitic ferrite, thereby ensuring a predetermined area ratio of retained austenite. Here, if the holding time in the holding temperature range is 80 seconds or more, the area ratio of bainitic ferrite may increase excessively, and the YS may decrease. In addition, excessive diffusion of C from bainitic ferrite to untransformed austenite may occur, and the area ratio of retained austenite may exceed 15.0%, making it difficult to achieve the desired YS and bendability. Therefore, the holding time in the holding temperature range is preferably less than 80 seconds. The holding time in the holding temperature range is more preferably less than 60 seconds.
[0110] (cooling process) Next, the steel sheet after the rapid heating step (after the holding step if the steel sheet is subjected to the holding step) is cooled to a cooling stop temperature of 100°C or higher and 300°C or lower.
[0111] Cooling stop temperature: 100℃ or more and 300℃ or less The cooling process is necessary to control the area ratio of tempered martensite and the area ratio of retained austenite generated in the subsequent reheating and holding process within a predetermined range. If the cooling stop temperature is less than 100°C, the untransformed austenite present in the steel is transformed into martensite almost entirely in the cooling process. This results in an excessive increase in the area ratio of tempered martensite, making it difficult to obtain an area ratio of retained austenite of 3.0% or more, and reducing ductility. On the other hand, if the cooling end temperature exceeds 300°C, the area ratio of tempered martensite decreases and the area ratio of fresh martensite increases. As a result, the desired YS may not be obtained. In addition, the YR decreases. Furthermore, there is a risk that the bendability cannot be achieved. Therefore, the cooling stop temperature is set to 100° C. or higher and 300° C. or lower. The cooling stop temperature is preferably 120° C. or higher. Also, the cooling stop temperature is preferably 280° C. or lower.
[0112] (Zinc plating process (hot-dip galvanizing process, alloying process)) During the above cooling step, after the cooling step and before the reheating and holding step, or after the reheating and holding step, the steel sheet may be subjected to a galvanizing treatment (hot-dip galvanizing, or further, alloyed hot-dip galvanizing treatment). By performing the galvanizing treatment, a galvanized steel sheet can be obtained. Examples of the galvanizing treatment here include hot-dip galvanizing treatment and alloyed galvanizing treatment (hot-dip galvanizing treatment and alloying treatment). When galvanizing is performed during the cooling step, it is preferable to cool the steel sheet to a bath temperature of 440 to 500° C. before carrying out the galvanizing. A hot-dip galvanized steel sheet can be obtained by subjecting a steel sheet to a hot-dip galvanizing treatment, and a galvannealed steel sheet can be obtained by further subjecting the steel sheet to an alloying treatment. Hereinafter, the hot-dip galvanizing treatment and the alloying treatment will be collectively referred to as a galvannealed treatment.
[0113] In the case of hot-dip galvanizing, it is preferable to immerse the steel sheet in a hot-dip galvanizing bath at 440°C to 500°C, and then adjust the coating weight by gas wiping or the like. The hot-dip galvanizing bath is not particularly limited as long as it has the composition of the zinc-coated layer described above, but it is preferable to use a plating bath with an Al content of 0.10 mass% or more, with the balance being Zn and unavoidable impurities. The Al content is preferably 0.23 mass% or less.
[0114] In the case of galvannealing treatment, it is preferable to carry out alloying treatment by heating the galvanized steel sheet to an alloying temperature of 450° C. or more after carrying out the galvannealing treatment as described above. The alloying temperature is preferably 600° C. or less. If the alloying temperature is less than 450°C, the Zn-Fe alloying rate is slow, and alloying may be difficult. On the other hand, if the alloying temperature exceeds 600°C, untransformed austenite is transformed into pearlite, making it difficult to achieve a TS of 1180 MPa or more, and ductility is reduced. The alloying temperature is more preferably 470°C or more. Also, the alloying temperature is more preferably 570°C or less.
[0115] In addition, the coating weight of both hot-dip galvanized steel sheet (GI) and galvannealed steel sheet (GA) is 20 g / m per side. 2 The coating weight of the zinc-plated layer on one side is preferably 80 g / m or more. 2 It is preferable that the plating thickness is set to be equal to or less than 100 nm. The plating thickness can be adjusted by gas wiping or the like.
[0116] (Reheating and holding process) Next, the steel sheet is reheated to a tempering temperature range of 460°C or lower (hereinafter also referred to as reheating temperature range), and the steel sheet is held in the tempering temperature range of 460°C or lower for a tempering time of 10 seconds to 2000 seconds. This tempers the martensite present in the steel at the end of the cooling process, and also causes the carbon that is supersaturated in the martensite to diffuse into the untransformed austenite, forming austenite that is stable at room temperature, i.e., retained austenite.
[0117] Tempering temperature (reheating temperature): 460℃ or less If the tempering temperature (reheating temperature) exceeds 460°C, the martensite present in the steel at the end of the cooling process will be excessively tempered, making it difficult to achieve a TS of 1180 MPa or more. In addition, the untransformed austenite present in the steel at the end of the cooling process will decompose into carbide (pearlite), reducing ductility. Therefore, the tempering temperature (reheating temperature) is set to 460° C. or less. The tempering temperature is the maximum temperature reached in the reheating and holding step. The tempering temperature is preferably 450° C. or less, and more preferably 440° C. or less. Although there is no particular lower limit for the tempering temperature (reheating temperature), if the tempering temperature is below 300°C, the martensite present in the steel at the end of the cooling process may not be tempered sufficiently, and fresh martensite may increase excessively. As a result, the desired YS may not be achieved. Furthermore, there is a risk that the bendability may not be achieved. Therefore, the tempering temperature is preferably above 300°C, more preferably above 320°C.
[0118] Tempering time in the reheating temperature range (holding time): 10 seconds or more and 2000 seconds or less If the tempering time (holding time) in the reheating temperature range is less than 10 seconds, the tempering of the martensite present in the steel at the end of the cooling process does not proceed sufficiently, and fresh martensite increases excessively. In addition, the coarsening of the carbides in the tempered martensite does not proceed sufficiently, and the density of the carbides in the tempered martensite may exceed a predetermined amount. As a result, the desired YS may not be achieved. In addition, the YR may decrease. Furthermore, there is a risk that the bendability may not be achieved. On the other hand, if the tempering time (holding time) in the reheating temperature range exceeds 2000 seconds, the tempering of martensite present in the steel at the end of the cooling process proceeds excessively, making it difficult to achieve a TS of 1180 MPa or more. In addition, the untransformed austenite present in the steel at the end of the second cooling process decomposes as carbide (pearlite), resulting in a decrease in ductility. Therefore, the tempering time (holding time) in the reheating temperature range is set to 10 seconds or more and 2000 seconds or less. The tempering time is preferably 20 seconds or more, more preferably 30 seconds or more. The tempering time is preferably 1000 seconds or less, more preferably 900 seconds or less. The tempering time (holding time) in the reheating temperature range includes not only the holding time at the reheating temperature, but also the residence time in that temperature range during heating and cooling before and after reaching the reheating temperature.
[0119] The cooling conditions after holding in the reheating temperature range are not particularly limited, and may be in accordance with a conventional method. For example, gas jet cooling, mist cooling, roll cooling, water cooling, and air cooling can be used as the cooling method. In addition, from the viewpoint of preventing oxidation of the surface, it is preferable to cool to 50°C or less after holding in the reheating temperature range, and more preferably to about room temperature. The average cooling rate in the cooling after holding in the reheating temperature range is preferably, for example, 1°C / sec or more. In addition, this average cooling rate is preferably 50°C / sec or less.
[0120] (Zinc plating process (electrolytic zinc plating process)) After cooling to room temperature, an electrogalvanizing treatment may be performed. By performing an electrogalvanizing treatment on the steel sheet, an electrogalvanized steel sheet can be obtained. When performing an electrogalvanizing treatment on the steel sheet surface, the treatment conditions for the electrogalvanizing treatment are not particularly limited, and may be performed according to a conventional method.
[0121] The steel sheet obtained as described above may be further subjected to temper rolling. If the reduction rate of temper rolling exceeds 2.00%, the yield stress increases, and the dimensional accuracy may decrease when the steel sheet is formed into a member. Therefore, the reduction rate of temper rolling is preferably 2.00% or less. The lower limit of the reduction rate of temper rolling is not particularly limited, but is preferably 0.05% or more from the viewpoint of productivity. The temper rolling may be performed on an apparatus continuous with the annealing apparatus for performing each of the above-mentioned steps (online), or may be performed on an apparatus discontinuous with the annealing apparatus for performing each of the steps (offline). The number of rolling times of temper rolling may be one or two or more. As long as the same elongation rate as that of temper rolling can be imparted, rolling using a leveler or the like may be used.
[0122] The other conditions than those mentioned above are not particularly limited, and may be those according to conventional methods.
[0123] [3. Materials] Next, a member according to one embodiment of the present invention will be described. A member according to one embodiment of the present invention is a member made using the above-mentioned steel plate (as a raw material). For example, the raw material steel plate is subjected to at least one of forming and joining to form a member. Here, the above steel plate has a TS of 1180 MPa or more, and has a high YS, a high YR, and excellent ductility, bendability, and energy absorption properties. Therefore, the member according to one embodiment of the present invention has high strength and excellent impact resistance properties. Therefore, the member according to one embodiment of the present invention is particularly suitable for application to impact energy absorbing members used in the automotive field.
[0124] [4. Manufacturing methods for components] Next, a method for manufacturing a member according to one embodiment of the present invention will be described. A method for manufacturing a component according to one embodiment of the present invention includes a step of subjecting the above-mentioned steel plate (e.g., a steel plate manufactured by the above-mentioned steel plate manufacturing method) to at least one of forming and joining to form a component. Here, the molding method is not particularly limited, and for example, a general processing method such as press processing can be used. The joining method is also not particularly limited, and for example, general welding such as spot welding, laser welding, and arc welding, rivet joining, crimp joining, etc. The molding conditions and joining conditions are not particularly limited, and may be in accordance with ordinary methods. EXAMPLES
[0125] Steel materials having the composition shown in Table 1 (the balance being Fe and unavoidable impurities) were melted in a converter and made into steel slabs by a continuous casting method. In Table 1, "-" indicates the content of unavoidable impurities.
[0126] The obtained steel slab was heated to 1200°C, and after heating, the steel slab was subjected to hot rolling consisting of rough rolling and finish rolling at a finish rolling temperature of 900°C to obtain a hot-rolled steel sheet. Next, the obtained hot-rolled steel sheets except for No. 67 were subjected to pickling and cold rolling (reduction rate: 50%) to obtain cold-rolled steel sheets having the thicknesses shown in Table 3. The obtained cold-rolled steel sheet was then subjected to an annealing step, a rapid heating step, a cooling step, a galvanizing step, and a reheating and holding step under the conditions shown in Table 2 to obtain a steel sheet (galvanized steel sheet). Note that, for No. 66, a holding step was performed after the rapid heating step and before the cooling step. The holding step conditions were a holding temperature of 480° C. and a holding time of 60 seconds.
[0127] Here, in the galvanizing process, a hot-dip galvanizing process, a galvannealed galvanizing process, or an electrogalvanizing process is performed to obtain a hot-dip galvanized steel sheet (hereinafter also referred to as GI), an alloyed hot-dip galvanized steel sheet (hereinafter also referred to as GA), or an electrogalvanized steel sheet (hereinafter also referred to as EG). The hot-dip galvanizing treatment and the galvannealing treatment were carried out after the cooling step and before the reheating and holding step, and the electrolytic galvanizing treatment was carried out after the reheating and holding step. In Table 2, the type of plating process is also indicated as "GI," "GA," or "EG." In Table 2, for GI and EG steel sheets, alloying treatment is not performed, so the alloying temperature is indicated as -. Also, in Table 2, cold-rolled steel sheets that were not zinc-plated in the zinc plating process are indicated as "CR."
[0128] The galvanizing bath temperature was 470°C for all of the production of EG, GI, and GA. The amount of zinc coating is 10 to 100 g / m when manufacturing EG. 2 When manufacturing GI, the weight is set at 45 to 72 g / m per side. 2 When manufacturing GA, the thickness is 45 g / m per side. 2 It was decided. The composition of the zinc plating layer of the finally obtained zinc-plated steel sheet was as follows: GI: 0.1-1.0 mass% Fe, 0.2-0.33 mass% Al, and the balance was Zn and unavoidable impurities; GA: 8.0-12.0 mass% Fe, 0.1-0.23 mass% Al, and the balance was Zn and unavoidable impurities; EG: 9.0-25.0 mass% Ni, and the balance was Zn and unavoidable impurities. In addition, the zinc plating layers were formed on both sides of the base steel sheet in each case.
[0129] The steel structure of the obtained steel sheet was identified in the manner described above. The measurement results are shown in Table 3. In Table 3, F is ferrite, BF is bainitic ferrite, TM is tempered martensite, RA is retained austenite, FM is fresh martensite, LB is lower bainite, and θ is carbide. In addition, in the manner described above, the surface layer in which the total area ratio of structures other than ferrite is ½ or less at the ¼ position of the sheet thickness was defined as the soft surface layer.
[0130] In addition, tensile tests and VDA bending tests were conducted according to the following procedures, and the tensile strength (TS), yield stress (YS), yield ratio (YR), total elongation (El), limit bending angle (α) in the VDA bending test, bending deformation absorbed energy amount, and production efficiency (E) were evaluated according to the following criteria.
[0131] ·TS 〇 (Pass): 1180MPa or more and less than 1470MPa × (Fail): Less than 1180MPa or more than 1470MPa
[0132] YS 〇(Pass): (A) When 1180MPa≦TS<1320MPa, 750MPa≦YS (B) When TS is 1320MPa or less, YS is 850MPa or less ×(Fail): (A) When 1180MPa≦TS<1320MPa, 750MPa>YS (B) When 1320MPa≦TS, 850MPa>YS
[0133] ·YR 〇(Pass): 0.70 or higher × (Fail): Less than 0.70
[0134] ·El 〇(Pass): (A) When 1180MPa≦TS<1320MPa, 11.0%≦El (B) 1320MPa≦TS, 9.0%≦El ×(Fail): (A) When 1180MPa≦TS<1320MPa, 11.0%>El (B) When 1320MPa≦TS, 9.0%>El
[0135] α 〇(Pass): 80° or more × (Fail): Less than 80°
[0136] ·AE 〇 (Pass): The integral value of the load-stroke curve is 70,000 N·mm or more × (Pass): The integral value of the load-stroke curve is less than 70,000 N mm
[0137] Production efficiency E(ton / h)=LS×t×W×ρ×60×10 ―6 Pass(A):16.0 <E<190.0 Pass(B):3.0 <E≦16.0、または190.0≦E<390.0 Pass (C): 3.0≧E or E≧390.0 Where: LS: Strip threading speed in the annealing process (m / min) t: Plate thickness (mm) W: Board width (mm) ρ: specific gravity of iron (ton / m 3 ) and ρ = 7.86 (ton / m 3 ).
[0138] (1) Tensile test The tensile test was performed in accordance with JIS Z 2241 (2011). That is, JIS No. 5 test pieces were taken from the obtained steel sheets so that the longitudinal direction was perpendicular to the rolling direction of the base steel sheet. Using the taken test pieces, a tensile test was performed at a crosshead speed of 10 mm / min, and TS, YS and El were measured. The results are shown in Table 4.
[0139] (2) VDA bending test The VDA bending test was performed in accordance with the VDA standard (VDA238-100) prescribed by the German Association of the Automotive Industry. Specifically, a test piece of 70 mm × 60 mm was taken from the obtained steel plate by shearing, where the 60 mm side was parallel to the rolling (L) direction. The test piece was subjected to a VDA bending test under the following conditions. Test method: Roll support, punch intrusion Roll diameter: φ30mm Punch tip R: 0.4 mm Distance between rolls: (sheet thickness x 2) + 0.5 mm Stroke speed: 20mm / min Bending direction: perpendicular to rolling (C) direction At this time, the angle of the outer bend at the center of the plate-shaped test piece when the load F from the pushing bending jig from above is maximum is measured as the bending angle (limit bending angle) (°). In addition, the integral value (absorbed energy) of the load-stroke curve up to the maximum load is calculated using the obtained load-stroke curve. The average values of the limit bending angle and the integral value (absorbed energy) of the load-stroke curve at the maximum load when the above VDA bending test is performed three times are respectively designated as α (°) and AE. The results are shown in Table 4.
[0140] In the VDA bending tests of steel plates with a thickness of over 1.2 mm, the effect of plate thickness was taken into consideration and all tests were conducted with steel plates with a thickness of 1.2 mm. Steel plates with a thickness of over 1.2 mm were ground on one side to make the thickness 1.2 mm. Since the grinding process may affect the bendability of the steel plate surface, the ground surface was placed on the inside of the bend (the side that comes into contact with the punch) in the VDA bending tests. On the other hand, in the VDA bending test of steel plates with a thickness of less than 1.2 mm, the effect of the plate thickness was small, so the test was performed without grinding.
[0141] [Table 1]
[0142] [Table 2-1]
[0143] [Table 2-2]
[0144] [Table 3-1]
[0145] [Table 3-2]
[0146] [Table 4-1]
[0147] [Table 4-2]
[0148] In Tables 1 to 4, the underlined parts indicate values outside the appropriate range of the present invention. As shown in Table 4, all of the inventive examples passed the test in terms of tensile strength (TS), yield stress (YS), yield ratio (YR), total elongation (El), limit bending angle (α) in the VDA bending test, and integral value (absorbed energy) (AE) of the load-stroke curve in the VDA bending test. In addition, the production efficiency (E) was also good. On the other hand, in the comparative examples, at least one of the tensile strength (TS), yield stress (YS), yield ratio (YR), total elongation (El), limit bending angle (α) in the VDA bending test, and integral value of the load-stroke curve in the VDA bending test (absorbed energy) AE) was insufficient.
[0149] In addition, the steel sheets of the present invention were used to form or join components, and all of the components had the excellent properties characteristic of the present invention, including tensile strength (TS), yield stress (YS), yield ratio (YR), total elongation (El), limit bending angle (α) in the VDA bending test, and integral value (absorbed energy) (AE) of the load-stroke curve in the VDA bending test. It was also found that the production efficiency (E) was good. [Explanation of symbols]
[0150] F Ferrite BF Bainitic ferrite TM Tempered martensite H Hard second phase L F―MA Length of the ferrite grain boundary in contact with fresh martensite and / or retained austenite
Claims
1. A steel plate comprising a base steel plate, the base steel plate comprising: In mass percent, C: 0.050% or more and 0.400% or less, Si: 0.20% or more and 3.00% or less, Mn: 1.00% or more and less than 3.50%; P: 0.001% or more and 0.100% or less, S: 0.0001% or more and 0.0200% or less, Al: 0.010% or more and 2.000% or less; N: 0.0100% or less and the balance being Fe and unavoidable impurities; The structure at 1 / 4 of the sheet thickness of the base steel sheet is as follows: Area ratio of ferrite: 8.9% or more and less than 20.0%, Area ratio of retained austenite: 3.0% or more and 15.0% or less, Area ratio of fresh martensite: 10.0% or less (including 0.0%), Total area ratio of bainitic ferrite and tempered martensite: 45.0% or more and 90.0% or less; The grain boundary length L of the ferrite grain boundary in contact with fresh martensite and / or retained austenite F―MA and the grain boundary length L of ferrite F Regarding L F―MA / L F : A steel structure satisfying 0.70 or less, having Furthermore, the layer is formed to a thickness of 20 μm or more in the thickness direction from the surface of the base steel sheet, The steel structure has a surface soft layer in which the total area ratio of structures other than ferrite in the steel structure is 1 / 2 or less at a 1 / 4 position of the plate thickness, A steel plate having a tensile strength of 1180 MPa or more and less than 1470 MPa.
2. The composition further includes, in mass%, Nb: 0.200% or less, Ti: 0.200% or less, V: 0.200% or less, B: 0.0100% or less, Cr: 1.000% or less, Ni: 1.000% or less, Mo: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Cu: 1.000% or less, Ta: 0.100% or less, W: 0.500% or less, Mg: 0.0200% or less, Zn: 0.0200% or less, Co: 0.0200% or less, Zr: 0.1000% or less, Ca: 0.0200% or less, Se: 0.0200% or less, Te: 0.0200% or less, Ge: 0.0200% or less, As: 0.0500% or less, Sr: 0.0200% or less, Cs: 0.0200% or less, Hf: 0.0200% or less, Pb: 0.0200% or less, Bi: 0.0200% or less; REM: 0.0200% or less The steel sheet according to claim 1, comprising at least one selected from the following:
3. The steel sheet according to claim 1 , further comprising a zinc-plated layer on one or both sides of the base steel sheet.
4. The steel sheet according to claim 2 , further comprising a zinc-plated layer on one or both sides of the base steel sheet.
5. A member made using the steel plate according to any one of claims 1 to 4.
6. A hot rolling process in which a steel slab having the composition according to claim 1 or 2 is hot rolled to obtain a hot rolled steel sheet; A pickling process for pickling the hot-rolled steel sheet; An annealing process in which the steel sheet after the pickling process is heated and annealed under the conditions of an annealing temperature of 720°C to 860°C, a holding time of 20 seconds or more, and a dew point of -10°C or more in an atmosphere; A rapid heating process of rapidly heating the annealing temperature to the annealing temperature + 10 ° C. or higher at a temperature increase rate of 10 ° C. / sec or higher from the annealing temperature; A cooling process in which the steel sheet after the rapid heating process is cooled to a cooling stop temperature of 100°C or more and 300°C or less; The steel sheet after the cooling step is heated to a tempering temperature of 460° C. or less and held in the temperature range for a tempering time of 10 seconds to 2000 seconds. Or even The method includes a cold rolling step in which the steel sheet after the pickling step and before the annealing step is subjected to cold rolling with a rolling reduction of 20% to 80% to obtain a cold-rolled steel sheet. A steel plate having a base steel plate, The structure at 1 / 4 of the sheet thickness of the base steel sheet is as follows: Area ratio of ferrite: 8.9% or more and less than 20.0%, Area ratio of retained austenite: 3.0% or more and 15.0% or less, Area ratio of fresh martensite: 10.0% or less (including 0.0%), Total area ratio of bainitic ferrite and tempered martensite: 45.0% or more and 90.0% or less; a steel structure in which a grain boundary length L F-MA in contact with fresh martensite and / or retained austenite on a ferrite grain boundary and a grain boundary length L F of ferrite satisfy L F-MA / L F : 0.70 or less; having Furthermore, the layer is formed to a thickness of 20 μm or more in the thickness direction from the surface of the base steel sheet, The steel structure has a surface soft layer in which the total area ratio of structures other than ferrite in the steel structure is 1 / 2 or less at a 1 / 4 position of the plate thickness, A method for producing a steel plate having a tensile strength of 1180 MPa or more and less than 1470 MPa.
7. The method for producing a steel sheet according to claim 6, wherein a passing speed LS (m / min) of the steel sheet in the annealing step satisfies the following formula (1). 3.0 / (t×W×4.716×10 ―4 )<LS<390.0 / (t×W×4.716×10 ―4 ) …………Formula (1) Where: t: sheet thickness after pickling process and before annealing process (mm), W: Sheet width after pickling process and before annealing process (mm) It is.
8. The method for producing a steel sheet according to claim 6, which satisfies the following (A) or (B). (A) a hot-dip galvanizing step of immersing a steel sheet in a hot-dip galvanizing bath during the cooling step, after the cooling step and before the reheating and holding step, or after the reheating and holding step, to form a zinc-coated layer on the steel sheet; Alternatively, the method may further include an alloying treatment step of performing an alloying treatment on the steel sheet on which the zinc plating layer is formed. (B) After the reheating and holding step, the steel sheet is immersed in an electrolytic zinc plating bath to form a zinc plating layer on the steel sheet.
9. The method for producing a steel sheet according to claim 7, which satisfies the following (A) or (B). (A) a hot-dip galvanizing step of immersing a steel sheet in a hot-dip galvanizing bath during the cooling step, after the cooling step and before the reheating and holding step, or after the reheating and holding step, to form a zinc-coated layer on the steel sheet; Alternatively, the method may further include an alloying treatment step of performing an alloying treatment on the steel sheet on which the zinc plating layer is formed. (B) After the reheating and holding step, the steel sheet is immersed in an electrolytic zinc plating bath to form a zinc plating layer on the steel sheet.
10. A method for manufacturing a component, comprising a step of subjecting the steel plate according to any one of claims 1 to 4 to at least one of forming and joining to form a component.
Citation Information
Patent Citations
High-strength cold-rolled steel sheet, high-strength galvanized steel sheet, and high-strength alloying hot-dip galvanized steel sheet, excellent in bendability, and method for manufacturing the same
JP2013163827A
High strength hot rolled steel sheet excellent in processability and fatigue characteristic and its manufacturing method
JP2014173151A
Steel sheet, member, and methods for manufacturing these
WO2021200578A1
Steel sheet, member, and methods for producing same
WO2021200580A1
High-strength steel plate, high-strength plated steel plate, method for producing same, and member
WO2023032424A1